Practical intelligence and the virtues - Russell, Daniel C. (Oxford : Oxford University Press, 2009)
Daniel Russell develops the idea that a necessary part of virtue is practical intelligence, the skill of determining what the right (e.g. kind or fair) thing to do would be on a given occasion, which requires much time, experience and practice. This idea has a key role to play in contemporary virtue ethics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Virtue; Ethics